A type-II C2N/α-Te van der Waals heterojunction with improved optical properties by external perturbation. Issue 39 (25th September 2019) - Ma, Zhuang; Wang, Yusheng; Wei, Yuting; Li, Chong; Zhang, Xiuwen; Wang, Fei
Abstract : The C2 N/α-Te vdW heterojunction possessed a unique type-II band alignment, tunable band gap, improved optical absorption strength, and broad spectrum width (ultraviolet to near-infrared). Abstract : C2 N with uniform honeycomb holes and a nitrogen lattice, whose vacant sites are partially filled by C6 hexagons, has a great potential due to its editable properties. Here, by using first-principles calculations, a C2 N/α-Te van der Waals (vdW) heterojunction and its electronic properties modulated by a vertical strain and external electric field were systematically investigated. The results showed that the C2 N/α-Te vdW heterojunction had a unique type-II band alignment, whose indirect band gap value was 0.47/1.01 eV in DFT/HSE06. The band gap could be tuned by external perturbation from 0.49 eV to 1.16 eV in HSE06. A type-II to type-I transition occurred under an external electric field of 0.4 V Å −1 . Interestingly, the C2 N/α-Te vdW heterojunction possessed high optical absorption strength (∼10 5 ) and broad spectrum width (ultraviolet to near-infrared region). These results indicate that the C2 N/α-Te heterojunction is promising for photovoltaic applications.